Multiple primary cutaneous melanoma in the amazon region of Peru - Laureano Suárez, Rocío (2024)
We report an 82-year-old male from Iquitos, Amazon region of Peru, with a three-month history of mild-tomoderate painful skin lesions on the right lower limb. The clinical examination revealed four tumors of the right shin, exhibiting exophytic growth, verrucose appearance, and ulceration. Two subcutaneous nodules were noted. Enlarged inguinal lymphadenopathy was observed. The histopathological examination revealed a diagnosis of melanoma. This case emphasizes the need for comprehensive and multidisciplinary surveillance in regions with limited melanoma data leading to a subdiagnosis of this malignancy. Also, it highlights the importance of primary prevention such as sun protection in tropical areas to prevent cutaneous melanoma, advocating for increasing awareness and preventive measures.